Сатирична графіка Галичини як чинник урбанізації суспільства у середині ХІХ - на початку ХХ століття - Іжевський, А. (Інститут народознавства НАН України, 2008)
Classified humorously-satiric graphic arts are classified in Galicia as an important constituent of Ukrainian city folklore, its role is in urbanization of society.